COMPOSITE MANNOSYLATED NANOPARTICLE FORMULA DEVELOPMENT ON RIFAMPICIN DELIVERY SYSTEM - Rachmawati, Putriana
Background and objective: Mycobacterium tuberculosis (Mtb) is a pathogen that has ability to persistent inside human body without causing any symptom (latent phase tuberculosis). On Mtb surface, there is a mannose capped lipoarabinomannan (ManLAM) that mediates the interaction between bacteria and macrophages via mannose receptors. This study aimed to develop composite nanoparticle as delivery system of rifampicin, an antituberculosis dtug, with acemannan as targeting agent. Acemannan, the main component of Aloe vera, is saccharide with polymannose sttuctured. Hypothesis of this research is transfection of composite nanoparticle into macrophage can mimic those of Mtb using interaction between acemannan and mannose receptors. Methods: Acemannan was isolated using ethanol precipitation methods and hydrolyzed using HCI at elevated temperature. The isolate was then characterized using thin layer chromatography (TLC) and anthrone colorimetric reaction. An assay for quantitative determination of acemannan is using Congo red as complexing agent. Acemannan was then conjugated with chitosan using an amine reduction agent, sodium triacetoxiborohydrate. Chitosan-acemannan conjugate was characterized using infra red spectrophotometry (FTIR), TLC and capillary viscometer for detennination molecular weight changes. The optimization process began with producing of nanostructure lipid carrier (NLC) system for incorporating rifampicin- The components of oil phase consisted of oleic acid and stearyl alcohol that was dissolved in ethyl acetate. Rifampicin was dissolved into the oil phase and NLC stabilized by Tween 80. Formula' development was done by optimization the amount of surfactant, oil and lipid, and active substance. During the process, homogenization and sonication speed and duration were optimized. The preparation was further developed with chitosan-acemannan conjugate addition into NLC to form composite nanoparticle. The composite was fonned by linking oleic acid and stearyl alcohol in NLC with chitosan through electrostatic interaction. Composite nanoparticle was characterized by particle size, polydispersity index, zeta potential, and entrapment efficiency of rifampicin. In addition, rifampicin pH dependent in-vitro release at pH 5 and 7.4, stability and in vitro toxicity test were evaluated. The morphology was analyzed using TEM and confocal microscope. Result: The isolate showed similar characteristic with BiAloe as standard and the acemannan present was 82.78±3.6%. The conjugate vi showed wavelength number changes at amide band and also Schiff base formation revealed by FTIR. In this study, it was obtained the NLC size of 181.3±5.8 nm, polydispersity index of 0.317±0.42 and potential zeta of -4.48±2.1. When chitosan-acemannan conjugate was added, the composite nanoparticle size was increased to 315.2±4.3 nm with polydispersity index of 0.28±0.02 and potential zeta of 1.66±1.39. Rifampicin composite nanoparticle entrapment was more than 90%. Composite nanoparticle formation by mixing of chitosan-acemannan conjugate before NLC formation giving smaller size than conjugate adsorption after NLC formation. Rifampicin release from composite nanoparticle was higher in pH 5. The composite nanoparticle was non toxic against vero cells. Drying process using lyophilization technique did not give significant changes on particle size (p>0.05). Solid composite nanoparticle was stable at storage temperature 250C and 40C in terms of content and particle size after reconstitution. Composite nanoparticle showed homogenous size, spherical with NLC in the middle and surrounded by chitosan-acemannan conjugate. Conclusion: The optimum formula of composite nanoparticle was obtain and potential to enhance rimpaficin transfection into macrophage to kill Mtb in latent tuberculosis.